Peptide LCGA-17 Attenuates Behavioral and Neurochemical Deficits in Rodent Models of PTSD and Depression - Anton V. Malyshev; Iuliia A. Sukhanova; Valeria M. Ushakova; Yana A. Zorkina; Olga V. Abramova; Anna Y. Morozova; Eugene A. Zubkov; Nikita A. Mitkin; Vsevolod V. Pavshintsev; Igor I. Doronin; Vasilina R. Gedzun; Gennady A. Babkin; et al. (MDPI AG, 2022)
We have previously described the LCGA-17 peptide as a novel anxiolytic and antidepressant candidate that acts through the α2δ VGCC (voltage-gated calcium channel) subunit with putative synergism with GABA-A receptors. The current study tested the potential efficacy of acute and chronic intranasal (i.n.) LCGA-17 (0.05 mg/kg and 0.5 mg/kg) in rats on predator odor-induced conditioned place aversion (POCPA), a model of post-traumatic stress disorder (PTSD), and chronic unpredictable stress (CUS) that produce a range of behavioral and physiological changes that parallel symptoms of depression in humans. CUS and LCGA-17 treatment effects were tested in the sucrose preference (SPT) social interaction (SI), female urine sniffing (FUST), novelty-suppressed feeding (NSFT), and forced swim (FST) tests. Analysis of the catecholamines content in brain structures after CUS was carried out using HPLC. The efficacy of i.n. LCGA-17 was also assessed using the Elevated plus-maze (EPM) and FST. Acute LCGA-17 administration showed anxiolytic and antidepressant effects in EPM and FST, similar to diazepam and ketamine, respectively. In the POCPA study, LCGA-17 significantly reduced place aversion, with efficacy greater than doxazosin. After CUS, chronic LCGA-17 administration reversed stress-induced alterations in numerous behavioral tests (SI, FUST, SPT, and FST), producing significant anxiolytic and antidepressant effects. Finally, LCGA-17 restored the norepinephrine levels in the hippocampus following stress. Together, these results support the further development of the LCGA-17 peptide as a rapid-acting anxiolytic and antidepressant.